High resting energy expenditure, less fat-free mass, and less muscle strength in HIV-infected children: a matched, cross-sectional study - Franco-Oliva, Andrea; Pinzón-Navarro, Beatriz Adriana; Martínez-Soto-Holguín, Martha C.; León-Lara, Ximena; Ordoñez-Ortega, Javier; Pardo-Gutiérrez, Ana Laura; Guevara-Cruz, Martha; Avila-Nava, Azalia; García-Guzmán, Alda Daniela; Guevara-Pedraza, Laura; Medina-Vera, Isabel (Frontiers in Nutrition, 2023)
Background & Aims: Many improvements have been made in the treatment of HIV in pediatrics, however, challenges remain, such as achieving normal growth, body composition, and metabolism during treatment. Current nutritional recommendations are based on studies performed in adults, with limited data in HIV-infected pediatric population. Therefore, the aim of this study was to compare the resting energy expenditure (REE) of asymptomatic HIV-infected pediatric patients versus versus healthy counterparts, as well as to compare body composition, dietary intake, and physical activity between the groups.Methods: Cross-sectional study of asymptomatic HIV-infected children receiving antiretroviral therapy compared uninfected group, matched by age (± 6 months), sex and body mass index (± 0.5 z score). Participants were recruited between 2021 and 2022 as outpatients. In both groups, REE was determined by indirect calorimetry, body composition by bioelectrical impedance analysis and hand strength, measured by hydraulic hand dynamometer.Results: Seventy-eight participants were enrolled, n=39 HIV-infected and n=39 control group with a mean age of 11.6 ± 3.4 years old. REE was significantly higher in HIV group (1254.4 ± 334.7 kcal/day vs 1124.7 ± 321 kcal/day, p= 0.013) compared to control group. Fat free mass was lower in HIV group (28.2 ± 10.5 kg vs 32 ± 11.2 kg, p=0.001), also when index skeletal muscle was evaluated this trend continued (7.2 ± 1.2 vs 7.6 ± 1.5, p=0.04) and strength of the dominant hand was also lower (12 (8-18) kg vs 20 (10.5-26) kg, p< 0.0001).Children with asymptomatic HIV infection have higher REE compared to their uninfected peers. They also present decreased fat free mass, skeletal muscle mass index and muscle strength. These parameters should be considered during nutritional assessment in this population to have a favorable impact on nutritional status and growth.